Fatty acids, protein contents and metal composition of some feed crops from Turkey - Bakoglu, Adil; Bagci, Eyuep; Ciftci, Harun (Wfl Publ, 2009)
In the course of investigations of new sources of higher plant lipids, fatty acid and metal compositions of some feed crops - Vicia ervilia (bitter veitch), Lotus corniculatus, Onobrychis fallax, Trifolium aureum (golden clover), Trifolium repens (white clover) (Fabaceae)- from Turkey were investigated by using GC and ICP-OES system. All the legume crops showed the same pattern of fatty acids. The fatty acid composition of plants used as feed crops showed different saturated and unsaturated fatty acid concentrations. Linolenic, oleic, palmitic and linoleic acids were found as the abundant compounds. The seeds are rich in unusual fatty acids, protein and also some elements. The protein content ranged from 20.09 to 28.6% in bitter vetch and golden clover. Cu, Mn, Cr, Ni, Zn, Fe, Mg, At and Pb were detected in the crop seeds in different amounts. The proximate analysis indicated that the seeds contained Cu 4.93-12.59, Mn 10.17-20.0, Zn 33.67-54.48, Fe 51.6-372.8, Mg 258.2-793.2 and At 10.38-15.50 mu g g(-1), respectively. The results were discussed in means of nutrition, agricultural values and phytochemicals.
Keywords: Feed crops; protein contents; fatty acid; trace elements; GC; ICP-OES